Case Report: Expanding the spectrum of renal involvement in adult-onset still’s disease: a case of focal proliferative glomerulonephritis and ischemic nephropathy - Zhang, Lina; Song, Yan; Wang, Suxia; Li, Shengguang (Frontiers in Medicine, 2025)
Adult-onset Still’s disease (AOSD) is a rare systemic inflammatory disorder characterized by high spiking fever, evanescent rash, and arthritis. Renal involvement in AOSD is uncommon but clinically significant, with varied manifestations such as AA amyloidosis, thrombotic microangiopathy (TMA), and collapsing glomerulopathy. In this case report, we presented a unique instance of a 28-year-old female with AOSD complicated by both focal proliferative glomerulonephritis (FPGN) and ischemic nephropathy—two rare renal manifestations confirmed via renal biopsy. The patient exhibited persistent fever, joint pain, and proteinuria, which were unresponsive to initial antimicrobial treatment but showed marked improvement following corticosteroid and immunosuppressive therapy. This case expands the known spectrum of renal involvement in AOSD and underscores the importance of prompt identification and individualized therapy. We also provide a comparative analysis of reported renal pathologies in AOSD to enhance understanding and guide management strategies.